2003
DOI: 10.1210/en.2002-220819
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Inhibition by Ghrelin of Insulin Secretion in the Mouse

Abstract: Ghrelin is produced by stomach oxyntic cells and thought to be involved in the regulation of body weight and food intake. We demonstrate here that the peptide inhibits insulin secretion from overnight-incubated mouse islets in the presence of 8.3, 11.1, and 22.2 mmol/liter glucose. Ghrelin was most efficient at 1 nmol/liter and its effect disappeared by raising the dose more than 25 nmol/liter. Also, insulin secretion in the presence of high K(+) concentrations (20 mmol/liter) was inhibited by ghrelin. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
180
3
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(207 citation statements)
references
References 26 publications
17
180
3
7
Order By: Relevance
“…Second, we have demonstrated that, in two mouse models, an early block in the differentiation of insulin-producing ␤ cells leads to an enormous increase in ghrelin-producing cells, perhaps through a cell fate switch. Although the physiological role of ghrelin remains controversial, several studies have demonstrated that ghrelin functions to regulate insulin activity (28)(29)(30). Therefore, it is remarkable to find a genetic link between these two hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we have demonstrated that, in two mouse models, an early block in the differentiation of insulin-producing ␤ cells leads to an enormous increase in ghrelin-producing cells, perhaps through a cell fate switch. Although the physiological role of ghrelin remains controversial, several studies have demonstrated that ghrelin functions to regulate insulin activity (28)(29)(30). Therefore, it is remarkable to find a genetic link between these two hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggested that ghrelin either stimulates [18,19,22] or inhibits insulin secretion depending on the experimental condition [23,24]. There have been also some claims that insulin (and / or glucose) lowers circulating ghrelin [25].…”
Section: Ghrelin Level Versus Insulin Levelmentioning
confidence: 99%
“…Furthermore, many earlier studies showed that ghrelin has been shown to inhibit insulin release in some experimental situations [24,29]. However these inconsistencies may reflect species differences and/ or differences in experimental design as different doses, different times of observation and in vitro versus in vivo experiments [30,31].…”
Section: Ghrelin Level Versus Insulin Levelmentioning
confidence: 99%
“…Previously called islet-activating protein (IAP), PTX was shown to lower glucose levels in the bloodstream by increasing insulin secretion from β cells (7). The enhanced secretion resulted from the removal of tonic inhibition exerted by neurotransmitters/hormones, including adrenaline (8), galanin (9), and ghrelin (10). PTX catalyzes the ADP ribosylation of a carboxyl-terminal cysteine present in the α subunits of the G protein subgroup now referred to as G i /G o (11).…”
mentioning
confidence: 99%